Appraising Policy, legal and Institutional Frameworks used in promoting Sustainable Sanitation Management Approaches in Mavoko Municipality within Machakos County - Mutua, Juliana Kamanthe; Agwata, Dr Jones; Anyango, Stephen; Oguge, Nicholas (Advances in Social Sciences Research Journal, 2018)
The objective of the study was to appraise the existing policies, legal and institutional frameworks and their influence in promoting sustainable sanitation management. The study site covered the urbanizing areas of Athi River, Katani, Kinanie, Mlolongo and Syokimau. A cross sectional study design was adopted and both quantitative and qualitative data collected to achieve the objectives of the study. 385 house hold respondents were interviewed. Simple random and purposive sampling methods were used to administer household questionnaires to standalone houses and comprehensive housing schemes. Interviews with Key Informants from the National Government, County Government of Machakos, Mavoko Water and Sewerage Company and Export Processing Zone Authority among other service providers were conducted. Quantitative data was analyzed using descriptive statistics and presented in tables, frequencies and percentages. A content analysis from qualitative data was developed to come up with thematic issues from the interviews. The study established that Residents were not aware of relevant policies on sanitation management, were not complying with the provisions of the Laws on sanitation management while the institutional frameworks were performing poorly due to institutional overlaps and differences. There are negligible budgetary provisions for the sanitation sector and these factors have hindered the desired impact to bring positive change for sanitation management approaches used in the area. Key recommendations made are to sensitize and raise Residents awareness on the policies and laws that provide for sanitation management, clarify mandates of Institutions providing services in the municipality and increase budgetary allocations to sanitation.